2007
DOI: 10.1111/j.1532-5415.2007.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing in Palliative Care as Death Approaches

Abstract: Prescribing changes as life-limiting illnesses progress, with older people taking more medications. Medications for comorbid medical conditions should be reviewed in the context of their original therapeutic goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
189
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(209 citation statements)
references
References 28 publications
14
189
0
6
Order By: Relevance
“…The post-death data collection indicated that there was a decrease in the proportion of never appropriate medications and an increase in the proportion of always appropriate medications for those residents who died during the study period. This is noteworthy despite the small number of residents involved; it may suggest a move away from curative goals of therapy towards palliative management of symptoms, as has been observed in other studies [3,20,21,45].…”
Section: Discussionsupporting
confidence: 51%
“…The post-death data collection indicated that there was a decrease in the proportion of never appropriate medications and an increase in the proportion of always appropriate medications for those residents who died during the study period. This is noteworthy despite the small number of residents involved; it may suggest a move away from curative goals of therapy towards palliative management of symptoms, as has been observed in other studies [3,20,21,45].…”
Section: Discussionsupporting
confidence: 51%
“…(6) Our findings are also consistent with a study by Currow et al that found consultative community and hospital based palliative care services reduced the number of medications for comorbid medical conditions by 1.1 per patient. (9) Finally, Garfinkel et al examined the impact of a consult service that used a geriatric-palliative care approach to improve drug use in older hospitalized patients. They found that they were able to discontinue one or more medications that lacked a valid or relevant indication, given the patient's age group and disability level, in 63% of 190 patients.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Previous successful strategies for reducing polypharmacy and/or unnecessary medication use in the elderly include an acute care geriatric evaluation and management team, (6) an interdisciplinary team in nursing home care, (7) a geriatric-palliative care algorithm, (8) and a consultative community and hospital based palliative care service. (9) In the one study in nursing homes, interdisciplinary team care resulted in the reduction of unnecessary medications per patient from 1.57 at admission to 0.34 at closeout. (7) The nation's largest integrated health care system, the Veterans Affairs (VA) Healthcare System, is intensely interested in optimizing care at the end of life and has greatly expanded its hospice and palliative care services, including those for older adults residing in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…One study, mostly in older patients with cancer, examined drugs prescribed at initial referral to a palliative service and monthly until death. 8 As death approached, the total number of drugs increased, with a decrease in drugs for comorbid conditions and an increase in drugs used to control symptoms. Many of the drugs used to control symptoms are classed as 'high risk' in older patients.…”
Section: Terminal Conditionsmentioning
confidence: 99%